ANALISIS PENGARUH VARIABEL-VARIABEL PADA MODEL UTAUT YANG DIMODIFIKASI TERHADAP PENGGUNAAN WEBSITE eCOMMERCE - Hari Moerti Endang Siti Astuti Imam Suyadi (SPIRIT, 2015)
Purpose – The Purpose of this research  was to analyze the use the Information System to the ecommerce website users with Unified Theory of Acceptance and Use of Technology (UTAUT) model approach. The objectives of this study in more specific were to: examine the effect of the Performance Expectancy, Effort Expectancy, Social Influence on the Behavioral Intention; examine the effect of the Facilitating Conditions, Behavioral Intention on the Use Behavior; examine the effect of Age as moderating variable;Methodology/approach -- This research is an explanatory research by using quantitative approach. Respondents in this study were 100 people who have filled out an online questionnaire. The sampling method of this study was a simple random sampling. The measurement scale used in this study was a semantic differential scale with a series of bipolar characteristics (two opposite polar) containing of a seven point scale, gradation from very negative to the left at the point 1 to the very positive right at the point 7. The data were then analyzed by using GSCA (Generalized Structured Component Analysis) method.Results -- (1) Performance Expectancy have significant effect on the Behavioral Intention; (1a) Performance Expectancy have negative and not significant effect on the Behavioral Intention moderated by Age; (2) Effort Expectancy have significant effect on the Behavioral Intention; (2a) Effort Expectancy have negative and not significant effect on the Behavioral Intention moderated by Age; (3) Social Influence has significant effect on the Behavioral Intention; (3a) Social Influence has positive and not significant effect on the Behavioral Intention moderated by Age; (4) Facilitating Conditions have significant effect on the Use Behavior; (4a) Facilitating Conditions have negative and not significant effect on the Use Behavior moderated by Age; and (5) Behavioral Intention has significant effect on the Behavioral Use;Findings -- The existence of moderating variable Age did not have a significant influence on the relationship among the other variables in this study. Keywords: UTAUT Model, The use of information system, eCommerce, Internet, Moderating Variable, Age, GSCA.